Beyond molecular recognition using a repulsive field to tune interfacial valency and binding specificity between adhesive surfaces - Santore, Maria M (Langmuir : the ACS journal of surfaces and colloids, 2009)
Surface-bound biomolecular fragments enable "smart" materials to recognize cells and other particles in applications ranging from tissue engineering and medical diagnostics to colloidal and nanoparticle assembly. Such smart surfaces are, however, limited in their design to biomolecular selectivity. This feature article demonstrates, using a completely nonbiological model system, how specificity can be achieved for particle (and cell) binding, employing surface designs where immobilized nanoscale adhesion elements are entirely nonselective. Fundamental principles are illustrated by a model experimental system where 11 nm cationic nanoparticles on a planar negative silica surface interact with flowing negative silica microspheres having 1.0 and 0.5 microm diameters. In these systems, the interfacial valency, defined as the number of cross-bonds needed to capture flowing particles, is tunable through ionic strength, which alters the range of the background repulsion and therefore the effective binding strength of the adhesive elements themselves. At high ionic strengths where long-range electrostatic repulsions are screened, single surface-bound nanoparticles capture microspheres, defining the univalent regime. At low ionic strengths, competing repulsions weaken the effective nanoparticle adhesion so that multiple nanoparticles are needed for microparticle capture. This article discusses important features of the univalent regime and then illustrates how multivalency produces interfacial-scale selectivity. The arguments are then generalized, providing a possible explanation for highly specific cell binding in nature, despite the degeneracy of adhesion molecules and cell types. The mechanism for the valency-related selectivity is further developed in the context of selective flocculation in the colloidal literature. Finally, results for multivalent binding are contrasted with the current thinking for interfacial design and the presentation of adhesion moieties on engineered surfaces